The boundaries of transnationalism: the case of assisted voluntary return migrants. (11th August 2016) - LIETAERT, INE; BROEKAERT, ERIC; DERLUYN, ILSE
Abstract: Few studies on transnationalism have focused on migrants who return to their country of origin with insufficient resources and limited mobility. This study sheds light on the transnational connections of those who went back to Georgia and Armenia from Belgium on a voluntary assisted return and reintegration programme. Using Boccagni's (2012) analytical framework, we reveal the returnees' interpersonal, institutional and symbolic transnational ties. Although these ties were often limited and had little effect on their daily lives, and although the migrants' desire to participate in the transnational field rarely matched their ability to do so, they nonetheless attached great value to them symbolically and emotionally. Our findings question current conceptualizations of transnationalism and the focus on the home country as the sole context in which transnational ties should have an impact. We believe that there is a need to pay greater attention to the subjective and symbolic dimensions of the return–transnationalism field, including the relationship between integration and return migration policies.